The importance of active search as a strategy in the screening of leprosy in the São José neighborhood, Imperatriz - MA (Research, Society and Development, 2022)
Objective: To track possible cases of leprosy through the active search in patients who are in vulnerable areas for transmission in the São José neighborhood, in the municipality of Imperatriz - MA. Methodology: This is a quantitative, exploratory study, which was developed based on a semi-structured questionnaire which addressed clinical symptoms along with risk factors, with objective questions personally applied to patients. Results: 53 people answered the questionnaire, with a predominance of females (74%), in addition to the majority without evident clinical manifestations (64%), although a reduced percentage of symptoms, the existence of associated risk factors such as the history of family as well as personal or residing close to patients previously diagnosed with the disease (28%). Conclusion: Based on the results obtained, it was found that some factors corroborate the spread of the disease, especially in areas with low socio economic status, however, the set of dermatological alterations presented did not result in the diagnosis of leprosy in the delimited area, however, observed different forms of dermatoses, supporting the active search as a method of early diagnosis not only in leprosy, but also in other pathologies.